2016
DOI: 10.1210/en.2015-1913
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Male Reproductive Endocrine Axis: Potential Role for a Delay Mechanism in the Inhibitory Action of Gonadal Steroids on GnRH Pulse Frequency

Abstract: We developed a compartmental model so we could test mechanistic concepts in the control of the male reproductive endocrine axis. Using SAAM II computer software and a bank of experimental data from male sheep, we began by modeling GnRH-LH feed-forward and LH-T feedback. A key assumption was that the primary control signal comes from a hypothetical neural network (the PULSAR) that emits a digital (pulsatile) signal of variable frequency that drives GnRH secretion in square wave-like pulses. This model produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…These animals become infected with ZIKV and high viral loads can be isolated from many organs including the testes [29,[33][34][35][36].Male sheep and humans share similar reproductive anatomy, including the presence of comparable accessory sex glands [37]. Thus, rams have been used as a model for the human male reproductive system, particularly with regards to endocrinology and embryology [38][39][40][41]. Recent work has shown that experimental infection of intact male sheep with bluetongue virus, a natural arbovirus of sheep, resulted in localization of the virus in the male reproductive tract and subsequent testicular degeneration, similar to pathology that can occur in ZIKV infection of male humans [42,43].…”
mentioning
confidence: 99%
“…These animals become infected with ZIKV and high viral loads can be isolated from many organs including the testes [29,[33][34][35][36].Male sheep and humans share similar reproductive anatomy, including the presence of comparable accessory sex glands [37]. Thus, rams have been used as a model for the human male reproductive system, particularly with regards to endocrinology and embryology [38][39][40][41]. Recent work has shown that experimental infection of intact male sheep with bluetongue virus, a natural arbovirus of sheep, resulted in localization of the virus in the male reproductive tract and subsequent testicular degeneration, similar to pathology that can occur in ZIKV infection of male humans [42,43].…”
mentioning
confidence: 99%
“…This theory allowed to demonstrate the existence of positive periodic solutions when parameters are replaced by fixed periodic functions. It is observed that the results are also valid in the absence of delays; however, the study of delayed systems is of great interest because as shown in [7], in many cases delayed models fit experimental data better, particularly when feedback is present.…”
Section: Summary and Discussionmentioning
confidence: 89%
“…For example in [3], a model is proposed that establishes in relation to the hours of response between an increase in GnRH (Gonadotropin-releasing hormone) secretion and a pituitary FSH (Follicle-stimulating hormone) response under dietary treatment or minutes for responses to sociosexual signs as we can see in [7].…”
Section: Introductionmentioning
confidence: 99%
“…This study suggests that part of the relaxing effect of E2 is independent of the Ca 2+ channel blockade. Under supraphysiological conditions, 17 β -oestradiol dilates the umbilical artery and vein [ 34 ]. 17 β -Oestradiol does not appear to decrease α -adrenergic system activity in SMCs in vivo [ 35 ].…”
Section: Discussionmentioning
confidence: 99%